2020
DOI: 10.1038/s41598-020-74133-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malassezia species on the skin of HIV-seropositive patients

Abstract: Malassezia is a genus of lipophilic yeasts residing on the skin of warm-blooded animals. The correlation between specific species and their involvement in skin diseases has been well researched. However, only very few studies have investigated the distribution of Malassezia spp. on the healthy skin of patients infected with human immunodeficiency virus (HIV). The purpose of this work was to analyze whether the composition of Malassezia spp. isolated from the skin of the HIV-infected patients differs from that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…However, the abundance of Malassezia within the gastrointestinal tract deserves a special attention, since most patients had relatively low CD4 cell counts [72]. HIV infection is associated with a depletion of CD4+ cells, especially in Th17 within the gastrointestinal tract [71,95]. Because Th17 cells are known to participate in the immunological response against Malassezia in the skin [71], this intestinal immune dysregulation in HIV patients may be one explanation for the overgrowth of Malassezia in the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the abundance of Malassezia within the gastrointestinal tract deserves a special attention, since most patients had relatively low CD4 cell counts [72]. HIV infection is associated with a depletion of CD4+ cells, especially in Th17 within the gastrointestinal tract [71,95]. Because Th17 cells are known to participate in the immunological response against Malassezia in the skin [71], this intestinal immune dysregulation in HIV patients may be one explanation for the overgrowth of Malassezia in the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…HIV infection is associated with a depletion of CD4+ cells, especially in Th17 within the gastrointestinal tract [71,95]. Because Th17 cells are known to participate in the immunological response against Malassezia in the skin [71], this intestinal immune dysregulation in HIV patients may be one explanation for the overgrowth of Malassezia in the gastrointestinal tract. This hypothesis remains to be confirmed in future studies which should focus on both the clinical and immunological impacts of the presence of Malassezia in the gastrointestinal tract of HIV patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the abundance of Malassezia within the gastrointestinal tract deserves a special attention, since most patients had relatively low CD4 cell counts [71]. HIV infection is associated with a depletion of CD4+ cells, especially in Th17 within the gastrointestinal tract [70,94]. Because Th17 cells are known to participate in the immunological response against Malassezia in the skin [70], this intestinal immune dysregulation in HIV patients may be one explanation for the overgrowth of Malassezia in the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Whether other non-immune factors related to HIV promote the overgrowth of Malassezia remains to be determined. Regarding the difference in the prevalence of Malassezia between HIV and non-HIV patients, a recent study reported a positive culture rate of 69% and 79% in 48 HIV and 48 non-HIV patients, respectively [70]. They found that patients with high CD4 cells had relatively high colonization rates, but the difference with the other groups was not statistically significant.…”
Section: Malassezia and Hiv Infectionmentioning
confidence: 97%